Histopathological Perspective of Linear and Whorled Nevoid Hypermelanosis in Adulthood: A Rare Case Report - Banyameen Iqbal; Srishti Malla; Tushar Kambale; Nayonikha Deokar (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
A rare pigmentation disorder called linear and whorled nevoid hypermelanosis (LWNH) is characterized by macular hyperpigmentation that follows the Blaschko lines. The cheeks, palms, soles, and mucosae are typically spared from lesions and are typically limited to the trunk, neck, and extremities. Although it is usually benign, there have been reports of associations with many congenital abnormalities. Herein, we present a rare case of LWNH involving the lateral surface of the abdomen in a 22-year-old male patient. A punch biopsy from the skin was received, and based on the histomorphological features, a diagnosis of LWNH was given. Hence, histopathology is the gold standard and confirmatory tool for definite diagnosis, along with other dermatological and genetic investigations in this case.